Ambroise, Cassiodore et la série dite de patriarchis - Gerzaguet, Camille (Revue d'études augustiniennes et patristiques, 2013)
A series of ambrosian treatises, firstly mentionned by Cassiodorus and entitled de patriarchis, has raised, from Lenain de Tillemont to latterly, various hypothesis regarding its composition. In the light of the discovery of the manuscript Lucca, biblioteca capitolare 14 (9th century), which contains a series of texts named as libri de patriarchis in its table of contents, and based on a reinterpretation of the meaning of liber in the three cassiodorian passages that refer to the series, this article aims to propose some elucidation about the identity and the order of the books which composed the succession of texts. This one would be due to a thematic edition, composed in Milan in the 5th or 6th century. Within the series, however, four treatises, De Isaac uel anima, De bono mortis, De fuga saeculi and De Iacob and uita beata, make up a tetralogy, whose thematic consistency and specific tradition in the manuscripts suggest a publication decided by Ambrose himself.